PENERAPAN MODEL PENANGANAN ANAK JALANAN MENURUT ARIEF RIZKA:Studi Di SD Negeri 6 Dobo Kabupaten Kepulauan Aru - Lazarus Boger (TANGKOLEH PUTAI, 2019)
This article examines the model of street child handling in Dobo, Southeast Maluku. The research method used is qualitative research methods. The data collection technique was done by observing, interviewing and observing. The research objectives: 1) Describe the condition of street children in SD Negeri 6 Dobo, Kepulauan Aru Regency, 2) Describe the application of handling street children according to Arief Rizka. The results of this study are as follows: 1) Street children in Dobo consist of: street children who are not taken care of by their parents, street children who have dropped out of school, street children who have never received education, street children who receive both physical and psychological violence from their parents and street children who do deviant behavior on the street. 2) The handling model is to go directly to the streets, build relationships, provide assistance, and follow up.